Juridical Analysis on Cabinet Structure Changes of Prabowo’s Government & The Impact to The New Government - Limbong, Andrew Afrizal; Simamora, Janpatar; Sihotang, Januari (Law Development Journal, 2025)
The cabinet structure is one of the important instruments in government, because it determines the pattern of executive work and the implementation of public policy, so that the formation of the cabinet is the president's first step in realizing his vision and mission through several selected people who will be part of his government cabinet. This study aims to analyze the juridical aspects of changes in the cabinet structure of President Prabowo's administration and its impact on governance in Indonesia using normative juridical research methods with a statutory approach. The results show that changes in the cabinet structure by President Prabowo are the prerogative of the President as stipulated in Article 4 paragraph (1) and Article 17 paragraph (2) of the 1945 Constitution of the Republic of Indonesia and Article 15 of Law No. 61 of 2024 concerning Amendments to Law No. 39 of 2008 concerning State Ministries. In terms of impact, changes in the cabinet structure have major implications for governance, especially on the efficiency of governance, where these changes can have a positive impact or even a negative impact depending on the work of each institution in the cabinet formed by President Prabowo.